Yiqi Huayu decoction alleviates bleomycin-induced pulmonary fibrosis in rats by inhibiting senescence - Zuo, Biao; Zuo, Ling; Du, Xu-Qin; Yuan, Su; Xuan, Chen; Zhang, Yu-Di; Chen, Zhi-Wei; Cao, Wen-Fu (Frontiers in Pharmacology, 2022)
Overview: In treating pulmonary fibrosis (PF), traditional Chinese medicine (TCM) has received much attention, but its mechanism is unclear. The pharmacological mechanisms of TCM can be explored through network pharmacology. However, due to its virtual screening properties, it still needs to be verified by in vitro or in vivo experiments. Therefore, we investigated the anti-PF mechanism of Yiqi Huayu Decoction (YHD) by combining network pharmacology with in vivo experiments. Methods: Firstly, we used classical bleomycin (BLM)-induced rat model of PF and administrated fibrotic rats with YHD (low-, medium-, and high-dose). We comprehensively assessed the treatment effect of YHD according to body weight, lung coefficient, lung function, and histopathologic examination. Second, we predict the potential targets by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) combined with network pharmacology. In brief, we obtained the chemical ingredients of YHD based on the UHPLC-MS/MS and TCMSP database. We collected drug targets from TCMSP, HERB, and Swiss target prediction databases based on active ingredients. Disease targets were acquired from drug libraries, Genecards, HERB, and TTD databases. The intersecting targets of drugs and disease were screened out. The STRING database can obtain protein-protein interaction (PPI) networks and hub target proteins. Molecular Complex Detection (MCODE) clustering analysis combined with enrichment analysis can explore the possible biological mechanisms of YHD. Enrichment analyses were conducted through the R package and the David database, including the Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), and Reactome. Then, we further validated the target genes and target proteins predicted by network pharmacology. Protein and gene expression detection by immunohistochemistry, Western blot (WB), and real-time quantitative PCR (rt-qPCR). Results: The results showed that high-dose YHD effectively attenuated BLM-induced lung injury and fibrosis in rats, as evidenced by improved lung function, relief of inflammatory response, and reduced collagen deposition. We screened nine core targets and cellular senescence pathways by UHPLC-MS/MS analysis and network pharmacology. We subsequently validated key targets of cellular senescence signaling pathways. WB and rt-qPCR indicated that high-dose YHD decreased protein and gene expression of senescence-related markers, including p53 (TP53), p21 (CDKN1A), and p16 (CDKN2A). Increased reactive oxygen species (ROS) are upstream triggers of the senescence program. The senescence-associated secretory phenotypes (SASPs), containing interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-α), and transforming growth factor-β1 (TGF-β1), can further exacerbate the progression of senescence. High-dose YHD inhibited ROS production in lung tissue and consistently reduced the SASPs expression in serum. Conclusion: Our study suggests that YHD improves lung pathological injury and lung function in PF rats. This protective effect may be related to the ability of YHD to inhibit cellular senescence.